Determination of serum lactate and glucose in dogs during swimming exercise - Korakot Nganvongpanit (2018)
The aims of this study were to investigate the levels of lactate and glucose in dogs during swimming and to determine the maximal lactate steady state in small and large breeds of dog. Twelve healthy dogs, including small breed (n = 6) and large breed (n = 6), were the study subjects. After swimming for different periods (5, 10, 15, 20, 25 and 30 min), blood was collected from the dogs which was then used to analyze changes in lactate and glucose levels during swimming. Results showed that the mean frequency of leg movement of the small breed was 99.7 ± 15.86 times/min, significantly higher (p < 0.05) than that of the large breed (71.72 ± 11.56 times/min). The levels of blood lactate and blood glucose in the two groups were not significantly different among the different exercise periods (p > 0.05). However, the highest level of serum lactate was found in the small breed after 15 min of swimming. In conclusion, in the large breed of dog 30 min swimming at this intensity did not increase the serum lactate up to the maximal lactate steady state, but in the small breed the maximal lactate steady state was achieved after 15 min of swimming.